KAOLIN POLYTYPE EVIDENCE FOR A HOT-FLUID PULSE ALONG CALEDONIAN THRUSTS DURING RIFTING OF THE EUROPEAN MARGIN - Parnell J.; Watt G.; Chen H.; Wycherley H.; Boyce A.; Elmore D.; Blumstein R.; Engel M.; Green P. (My University, 2004)
Sedimentary basins developed along the European margin during the earliest, Permian, stage of proto-Atlantic rifting, during a phase of high heat flow. The proximity of some basins to Caledonian thrusts has implied that rifts locally utilized the basement fabric. New mineralogical and palaeomagnetic data show that thrust planes in the Moine Thrust Zone channelled a Pulse of hot fluid in Permian time. The fluids precipitated kaolin in fractures in the thrust zone, and with decreasing intensity away from the zone. The high-temperature polytype dickite is largely confined to major thrust planes. Stable H and 0 isotope analyses indicate that the parent fluid included meteoric water involved in a hydrothermal system. Coeval hydrothermal hematite has a chemical remanence that dates the fluid pulse as Permian. This is direct evidence for post-orogenic activity in the thrust zone, in which the thrusts vented excess heat during regional crustal extension. The example from the European margin exemplifies the importance of deep-seated structures in the release of heat, and the value of kaolinite polytype mapping as a toot to record anomalous palaeo-heat flow.